2017
DOI: 10.4236/aa.2017.72008
|View full text |Cite
|
Sign up to set email alerts
|

The Geography as a Regulator of Genetic Flow and Genetic Structure in Andorra

Abstract: The Principality of Andorra is one of the smallest states in Europe. Traditionally its economy has been based on the agriculture and cattle ranch although in the last decades it has developed an important tourist activity that has become a collector of emigrants. The origin of marriage consorts has been analyzed in the six parishes that have traditionally constituted the Principality. In total, there have been 10,208 marriages covering a continuous period from 1606 to 1960. From this information, two migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We identified a total of 1675 HGT orthogroups in 22 nematodes. Placing these orthologues designated as events onto the species phylogeny assuming a parsimonious scenario (Campoy & González‐Martín, 2017) indicated that HGT started in the last common ancestor of clade IV nematodes (Figure 4a). Examples include GH16, GH32, GH43 and the aforementioned GH5 cellulases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a total of 1675 HGT orthogroups in 22 nematodes. Placing these orthologues designated as events onto the species phylogeny assuming a parsimonious scenario (Campoy & González‐Martín, 2017) indicated that HGT started in the last common ancestor of clade IV nematodes (Figure 4a). Examples include GH16, GH32, GH43 and the aforementioned GH5 cellulases.…”
Section: Resultsmentioning
confidence: 99%
“…Orthogroups having at least one gene with an AI value >30 were selected for further analysis. Gains and losses at each node were inferred using phylip‐dollop (Campoy & González‐Martín, 2017) (version 3.69; options: fdollop ‐method d ‐ancseq). Some of the HGT family‐acquired branches were manually curated by their evolutionary place in the gene phylogeny due to the fact that nematode genes with AI <0 were clustered with other HGT genes.…”
Section: Methodsmentioning
confidence: 99%
“…We identified a total of 1,675 HGT orthogroups in 22 nematodes. Placing these orthologs designated as events onto the species phylogeny assuming a parsimonious scenario (Campoy & González-Martín, 2017), indicated that HGT started in the last common ancestor of clade IV nematodes ( fig 4a ). Examples include GH16, GH32, GH43 and the aforementioned GH5 cellulases.…”
Section: Resultsmentioning
confidence: 99%
“…Orthogroups having at least one gene with an AI value over 30 were selected for further analysis. Gains and losses at each node were inferred using Phylip-Dollop (Campoy & González-Martín, 2017) (ver 3.69; options: fdollop -method d -ancseq). Some of the HGT family acquired branches were manually curated by their evolutionary place of gene phylogeny due to the fact that nematode genes with AI < 0 were clustered with other HGT genes.…”
Section: Methodsmentioning
confidence: 99%